Pengaruh Suku Bunga, Nilai Tukar, Dow Jones Industrial Average, dan Nikkei 225 terhadap Indeks Harga Saham Gabungan Periode 2017–2025 - Hilmi Fathur Rahman; Dicky Iranto; Tuty Sariwulan (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study analyzes the influence of interest rates, exchange rates, the Dow Jones Industrial Average (DJIA), and the Nikkei 225 on the Composite Stock Price Index (IHSG) in Indonesia during 2017–2025. Using quantitative approach with 108 monthly time series observations, the analysis employs multiple linear regression with Ordinary Least Squares (OLS) corrected using Newey-West HAC Standard Errors to address autocorrelation. The results show that interest rates have a positive and significant effect on the IHSG (t = 4.347; p = 0.000), while exchange rates have a negative and significant effect (t = -5.163; p = 0.000). The DJIA has no significant effect on the IHSG (t = -1.046; p = 0.298), indicating domestic factors play a more dominant role. The Nikkei 225 has a positive and significant effect (t = 14.093; p = 0.000), confirming strong linkages between Indonesian and Japanese capital markets. The adjusted R-squared of 88.29% indicates that the four independent variables explain 88.29% of IHSG movements. These findings confirm that domestic factors such as interest rates and exchange rates, as well as regional factors such as the Nikkei 225, have a more dominant role in influencing IHSG movements compared to global factors such as the DJIA.